Autophagy and immunity – insights from human herpesviruses - Williams, Luke; Taylor, Graham (Frontiers in Immunology, 2012)
The herpesviruses are a family of double-stranded DNA viruses that infect a wide variety of organisms. Having co-evolved with their hosts over millennia, herpesviruses have developed a large repertoire of mechanisms to manipulate normal cellular processes for their own benefit. Consequently, studies on these viruses have made important contributions to our understanding of fundamental biological processes. Here we describe recent research on the human herpesviruses that has contributed to our understanding of, and interactions between, viruses, autophagy, and the immune system. The ability of autophagy to degrade proteins located within the nucleus, the site of herpesvirus latency and replication, is also considered.